Mongolia Quarterly Economic Update, August 2011 - World Bank (Washington, DC, 2017)
The Mongolian economy is experiencing rapid growth in 2011 the second quarter saw the economy growing at a whopping 17.3 percent year on year, compared to 9.9 percent in the first quarter. Transportation and construction grew at 39.9 percent and 38.4 percent, respectively, while retail and wholesale trade grew at 24.7 percent, with Mongolians spending more on consumption as a result of higher incomes. The mining and manufacturing sectors recorded respectable growth rates of 8.3 and 12.9 percent yoy in the second quarter, respectively. Reflecting the higher growth, unemployment declined from 13 percent in December 2010 to 8.7 percent in June. Informal labor markets for unskilled workers are also booming, with real wages nearly doubling between December 2010 and June 2011. Mongolia's economic outlook depends heavily on global macroeconomic factors: the current uncertainty and poor growth prospects for the global economy are cause for concern. If there is another global recession, Mongolia's small, open economy will be affected. In that case, China's policy reaction will be crucial for Mongolia.